Inhibitior of Bcl6 by FX1 protects DSS induced colitis mice through anti-inflammatory effects - Liu, Ruixian; Zhang, Zhe; Zhou, Chuan; Wang, Binbin; Zhang, Muhan; Sun, Yaxing; Yao, Yao; Zhang, Yanru; He, Yijia; Yu, Junzhi; Xia, Yimeng; Liu, Yan; et al. (Frontiers in Immunology, 2025)
IntroductionInflammatory bowel disease (IBD) is a complex immune-mediated condition, and biologics are the most commonly used drugs for its treatment. However, there are still cases of ineffective treatment. B-cell lymphoma 6 (Bcl6), a transcriptional suppressor, is known to have regulatory effects on multiple immune-associated cell subsets. FX1, a novel specific BCL6 Bric-à-brac (BTB) inhibitor, has shown positive effects in many disease models, but its effects and mechanisms in IBD control remain unclear.MethodsWe observed colon length and DAI score of colitis mice after treatment. HE staining section was used to evaluate colonic injury, while the expression of colonic pro-inflammatory cytokines by RT-qPCR. And differences in immune cell subsets between the two groups was analyzed by flow cytometry. Additionally, IHC and RT-qPCR were employed to evaluate the expression of colonic tight junction proteins. Furthermore, RAW264.7 cells and co-cultured Caco2 cells were detected by ELISA and RT-qPCR.ResultsIn the treat group, colitis symptoms in mice were significantly improved, and there was a decrease in proportion of macrophages and protection of intestinal mucosal integrity-indicating anti-inflammatory effects of FX1. In cell experiments, we found that FX1 decreased secretion of pro-inflammatory factors by macrophages and increased expression of tight junction proteins in Caco2 cells after co-culture.DiscussionThe experimental findings demonstrate the inhibitory effect of FX1 on inflammation in murine colitis model as well as its potential mechanism. BCL6 is a potential target for treating IBD.